2013
DOI: 10.5799/ahinjs.01.2013.02.0263
|View full text |Cite
|
Sign up to set email alerts
|

Association of the sleep quality with pain, radiological damage, functional status and depressive symptoms in patients with knee osteoarthritis

Abstract: Objective: The aim of this study is to evaluate the sleep quality and relationship between the sleep quality with disease-related variables, pain, functional status, radiological damage and the psychological status in patients with Osteoarthritis (OA). Methods:Fifty two patients diagnosed with OA and 35 healthy control subjects were enrolled in the study. The demographic characteristics of the patients such as age, education level, and marital status were recorded. Disease related disability were assessed usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 16 publications
1
6
0
Order By: Relevance
“…Wilcox et al [27] included 429 knee OA patients and reported problems with sleep onset (31%), sleep maintenance (81%), and early morning awakenings (51%) occurred at least weekly. Sariyildiz et al [28] also included 52 knee OA patients and found significantly higher subjective sleep quality, falling asleep period, and usual sleep habit, and total PSQI scores in the patient group compared to the controls. In our study, consistent with these findings, we also observed that both groups had significantly worse sleep quality using the PQSI scale.…”
Section: Discussionmentioning
confidence: 98%
“…Wilcox et al [27] included 429 knee OA patients and reported problems with sleep onset (31%), sleep maintenance (81%), and early morning awakenings (51%) occurred at least weekly. Sariyildiz et al [28] also included 52 knee OA patients and found significantly higher subjective sleep quality, falling asleep period, and usual sleep habit, and total PSQI scores in the patient group compared to the controls. In our study, consistent with these findings, we also observed that both groups had significantly worse sleep quality using the PQSI scale.…”
Section: Discussionmentioning
confidence: 98%
“…Sleeplessness is a risk factor for fatigue in OA 5,8. The problem of sleeplessness can occur in most of the rheumatic diseases, and its main cause is pain 9. Pain that increases with activity and decreases at rest in the early stage of the disease becomes more intense and resistant as the disease progresses.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that arthritis affects sleep quality adversely. These studies have also shown that patients with arthritis have sleeping problems such as difficulty in falling asleep, frequent sleep disruption and early morning awakening 9,11,12. The literature review indicates that although the majority of studies have been conducted on sleep quality in patients with rheumatoid arthritis, the number of studies investigating sleep quality in patients with KOA is low 9.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations